2020
DOI: 10.1016/j.adolescence.2020.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and risky behaviors in adolescents: A meta‐analysis

Abstract: Introduction: This systematic review and meta-analysis examined the associations between social media use and risky behaviors during adolescence, and evaluated study characteristics (e.g., sample age, type of social media platform assessed) that may moderate these relationships.Methods: A comprehensive search strategy identified relevant studies from PsycInfo, PubMed, Google Scholar, and Proquest Dissertations and Theses Global. Results:The final sample included 27 independent cross-sectional studies with a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(179 citation statements)
references
References 122 publications
3
144
0
10
Order By: Relevance
“…Furthermore, some authors reported that messages posted on social media sites can promote health-damaging behavior, e.g., promoting anorexia [ 70 ]. Vannucci et al carried out a systematic review with meta-analysis on the association between social media use and risky behaviors in adolescents [ 71 ]. They found a small to medium correlations between the use of social media and engagement in risky behaviors in general and related to substance abuse and risky sexual activities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some authors reported that messages posted on social media sites can promote health-damaging behavior, e.g., promoting anorexia [ 70 ]. Vannucci et al carried out a systematic review with meta-analysis on the association between social media use and risky behaviors in adolescents [ 71 ]. They found a small to medium correlations between the use of social media and engagement in risky behaviors in general and related to substance abuse and risky sexual activities.…”
Section: Discussionmentioning
confidence: 99%
“…One exciting avenue for passive data sampling is understanding the role of social media usage as either risk or resilience markers for physical and mental health outcomes, including substance use. Social media use has been linked to psychopathology in adolescents, including higher symptoms of depression and anxiety [97]. However, previous research has not established screen time as a causal factor in the development of mental health outcomes, or whether altered social media use and screen time are a correlate or consequence of the development of psychopathology [98].…”
Section: Future Directionsmentioning
confidence: 99%
“…This is also a period that has been associated with the onset of risk behaviors (Defoe, Dubas, & Romer, (2010) that are maintained into adulthood and very often co-occur (Champion et al, (2019). Recent studies also highlight the links between social media use and risky behaviors during adolescence Vannucci, Simpson, Ggnon, & McCauley, (2020), but longitudinal data allow us to understand that adolescents who report frequently using social media face higher risks of mental health problems Riehm et al, (2019).…”
Section: Introductionmentioning
confidence: 99%